Analisis Pendampingan Operasional Homestay Desa Wisata Cibiru Wetan: Tantangan dan Solusi - Winda Gafrilia Prianka; Muhammad Syakib Asqalani Rifai; Revina Nurul Aini (Politeknik Piksi Ganesha Indonesia, 2025)
The community service program conducted in Cibiru Wetan Tourism Village, Bandung Regency, West Java, focused on operational assistance for homestays to improve service quality, strengthen operational standards, and enhance business sustainability. The activities were carried out through stages of socialization, training, evaluation, and the development of Standard Operating Procedures (SOPs) for homestays involving village officials, the DEWI tourism awareness group, homestay owners, and local youth. The results indicated a significant improvement in homestay managers’ knowledge and skills. Based on pre-test and post-test assessments, the average score increased by 35% in SOP knowledge, 28% in communication skills, and 29% in guest management. Additionally, a homestay SOP document was successfully developed as a guideline for 29 units, ensuring standardized services that were previously inconsistent. The program also improved tourist satisfaction, particularly in cleanliness (from 60% to 85%) and facilities (from 55% to 78%). Furthermore, it encouraged youth involvement in digital promotion, with 60% of local youth actively participating in online marketing and the introduction of a simple reservation system. However, challenges remain in financial record-keeping and digital literacy among managers. Thus, further programs focusing on financial management training, digital reservation systems, and continuous monitoring are required. Overall, this program successfully enhanced managerial capacity, strengthened service standards, and reinforced a competitive and sustainable community-based homestay management model.